Kajian Partisipasi dan Kelayakan Usaha Persemaian Jabon Merah (Anthocephalus macropyllus) (Studi Kasus Kelompok Tani Tunas Karumama Desa Tangkunei, Minahasa Selatan) - Nurhasni Sirajudin; Hengky D. Walangitan; Marthen Th. Lasut; Maria Y.M.A. Sumakud (Universitas Sam Ratulangi, 2013)
ABSTRACTThe purpose of this research are analyzing the level of members group participation, determining business impact to increase in household economy and analyzing the financial of nursery red Jabon of farmer group Tunas Karumama. This research was done in Tangkunei Village South Minahasa in April 2013. Data were collected using observation and census techniques, the analyzing of participation was using the Spearman Rank correlation and financial analysis of business use the B / C ratio. Descriptive analysis shows that the level of respondents participation 66.67 % was high participation, 23.81 % was moderate participation and Low participation was 9.52 %. The level of participation influenced by education. The economic aspect, activity of nursery was not increasing the household income. The results of analysis financial was using analysis of B / C Ratio value obtained 1,86 > 1,00. Financially this nursery was feasible.Key words : Education, Participation, Feasibility Of Businesses, Identity of Respondents.